1994
DOI: 10.1104/pp.105.3.927
|View full text |Cite
|
Sign up to set email alerts
|

Are Redox Reactions Involved in Regulation of K+ Channels in the Plasma Membrane of Limnobium stoloniferum Root Hairs?

Abstract: l h e effects of the impermeant electron acceptor hexacyanoferrate 111 (HCF 111) and the potassium channel blocker tetraethylammonium (TEA) on the current-voltage relationship and electrical potential across the plasma membrane of Limnobium stoloniferum root hairs was investigated using a modified sucrose gap technique.One millimolar HCF 111 immediately and reversibly depolarized the membrane by 27 mV, whereas the effect on the trans-membrane current was markedly delayed. After 6 min of treatment with this ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 22 publications
3
12
0
1
Order By: Relevance
“…(Grabov and B6ttger 1994). Our results would be consistent with e-acceptors causing membrane depolarization and then decreasing K + influx or even causing K + efflux, while edonors would cause hyperpolarization and then K § influx enhancement (see Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…(Grabov and B6ttger 1994). Our results would be consistent with e-acceptors causing membrane depolarization and then decreasing K + influx or even causing K + efflux, while edonors would cause hyperpolarization and then K § influx enhancement (see Fig.…”
Section: Discussionsupporting
confidence: 86%
“…One of the four subunits (gp91 ph~ of the transmembrane enzyme NADPH-oxidase of the PM redox chain of these cells has been identified as an H + pathway associated to this NADPH-oxidase (Henderson 2001). The redox activity generates changes in the PM electric potential that were secondarily responsible for changes in K § flux, by modulating the open or closed state of voltage-gated in-and outward K + channels (Grabov and B6ttger 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Research on plasma membrane redox activity suggests that plant cells are able to reduce exogenous electron acceptors; hexacyanoferrate III (HCF III) is much used in such studies [5][6][7][8]. Ferricyanide reduction by plant cells is accompanied by proton release [9][10][11] and plasma membrane depolarization [12,13]. It has also been reported that plant hormones of the auxin class change the rate of HCF III reduction and proton extrusion by plant cells [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…By contributing to the root surface area, root hairs are known to play an important role in the absorption of water and nutrients from the soil (Grabov and Bottger, 1994;Lauter et al, 1996;Gahoonia et al, 1997Gahoonia et al, , 2001White, 1998). Additionally, root hairs serve as a site of interaction for fungal and bacterial soil microorganisms, among them nitrogen-fixing bacteria, such as Rhizobium, Azorhizobium, and Bradyrhizobiumin (Mylona et al, 1995;Long, 1996).…”
mentioning
confidence: 99%